Grain amaranth, a potential and resilient food crop amenable to processing for diverse food and other products - Mng’omba, Simon A. (Frontiers in Sustainable Food Systems, 2025)
Grain amaranth remains a neglected and underutilized indigenous food crop (IFC) despite its diverse accessions in sub-Saharan Africa. This is in comparison with a few cereal crops providing carbohydrates and other nutrients, especially in southern Africa. Grain amaranth, a pseudocereal crop, is resilient to climate variability or change that has plagued southern Africa with frequent droughts, food and nutrition insecurity. The region experiences semi-arid to arid conditions and poor soil fertility which severely affect cereal crop production. These challenges demand an increase in cereal crops that are adaptable to local environments and amenable to processing methods to preserve food for the lean periods. One such IFC is grain amaranth which is adapted to many conditions and has a potential to be utilized in food, cosmetic, computer and pharmaceutical industries. The objective of this review was to describe the status of grain amaranth in terms of research and development with respect to production, nutritional benefits, processing and/or preservation, utilization and seed systems. Southern Africa was the focus of this review due to the prevalence of acute human hunger in this region and limitations in cereal crop production. The results show that grain amaranth on-farm or commercial production and seed systems are scarce in southern Africa. Field trials have shown wide grain yield variations between accessions although this provides an opportunity to select high yielding accessions. There are a few studies on drought tolerance to select accessions exhibiting this trait. Available processing methods show potential to add value to amaranth grain products and enable preservation, but this has not been fully exploited to benefit end users. A good seed system is needed to foster quality assurance and seed accessibility to potential growers. Increasing investments in research and development with farmers’ participation in the entire value chain would promote wider grain amaranth cultivation, processing and subsequent utilization. There is a need to test and develop grain amaranth accessions that are resilient to arid and frequent drought conditions and amenable to processing and preservation to improve cereal crop base, food and nutrition security in southern Africa.